Bidirectional communication between neural and immune systems. (25th December 2019) - Kamimura, Daisuke; Tanaka, Yuki; Hasebe, Rie; Murakami, Masaaki
Abstract: The immune and nervous systems share many features, including receptor and ligand expression, enabling efficient communication between the two. Accumulating evidence suggests that the communication is bidirectional, with the neural system regulating immune cell functions and vice versa . Steroid hormones from the hypothalamus–pituitary–adrenal gland axis are examples of systemic regulators for this communication. Neural reflexes describe regional regulation mechanisms that are a historically new concept that helps to explain how the neural and body systems including immune system communicate. Several recently identified neural reflexes, including the inflammatory reflex and gateway reflex, significantly impact the activation status of the immune system and are associated with inflammatory diseases and disorders. Either pro-inflammatory or anti-inflammatory effects can be elicited by these neural reflexes. On the other hand, the activities of immune cells during inflammation, for example the secretion of inflammatory mediators, can affect the functions of neuronal systems via neural reflexes and modulate biological outputs via specific neural pathways. In this review article, we discuss recent advances in the understanding of bidirectional neuro-immune interactions, with a particular focus on neural reflexes.